PELATIHAN BUDIDAYA SISTEM INTEGRASI PADA KONSTRUKSI KERAMBA JARING APUNG DI DESA TANGGETADA, KABUPATEN KOLAKA - Anti Landu; Bustang Bustang; Ilham Antariksa Tasabaramo; Yusnaini Yusnaini; Latifa Sekri; Asmadin Asmadin; Hasan Eldin Adimu; Simun Sukrin; Juhardin Juhardin (Jurnal Abdi Insani, 2025)
Tanggetada Village has significant fisheries potential, yet it remains underutilized by local fishermen. This is attributed to several factors, including limited infrastructure and the fishermen group’s lack of knowledge. Additionally, during poor weather conditions, fishermen lack alternative livelihoods beyond capture fishing. Therefore, aquaculture can serve as a viable solution to maintain their productivity. This community engagement initiative aims to enhance the knowledge and skills of the fishermen group in integrated aquaculture sistems using floating net cage construction. The activity was implemented in Tanggetada Village, Kolaka Regency, in collaboration with the Malaja Biru fishermen group. The methodology consisted of several stages: socialization, training, mentoring, and evaluation. The results of this activity demonstrated significant improvements in the knowledge and skills of the Malaja Biru fishermen group regarding integrated aquaculture in floating net cages. Twenty participants actively engaged in the outreach, training, and cage construction. Evaluation showed a knowledge increase from 50% to 100% and skill proficiency reaching 90–100%. Intensive mentoring and technology transfer methods effectively enhanced fishermen’s capacity, enabling them to independently and sustainably cultivate grouper, lobster, and pearl oysters using integrated aquaculture systems. It can be concluded that the 2024 Kosabangsa community service program successfully enhanced the capacity of the Malaja Biru Fishermen Group in Tanggetada Village through training in integrated aquaculture using floating net cage systems..